EFISIENSI PEMANFAATAN LAHAN UNTUK PENINGKATAN PRODUKSI PERTANIAN PADI DI DESA LAKEKUN KECAMATAN KOBALIMA KABUPATEN MALAKA - Lalak, Maria Virginia; Wulakada, Hamza Huri; Sukmawati, Sukmawati (Jurnal Geografi, 2025)
The condition of rice field agricultural land in Lakekun Village has experienced a decrease in harvest yields, rice fields do not receive water supply through irrigation channels causing planting failure and harvest failure. The purpose of the study (1) To determine the level of intensification of the use of rice agricultural land in Lakekun Village in an effort to increase production, (2) To determine the carrying capacity of land for agricultural productivity, (3) To determine the increase in land quality. This research method is a quantitative method and a qualitative approach. The results of the study (1) Intensification applied by farmers through the selection and use of superior seeds such as ciherang, impari and seeds from the harvest, proper land management, good fertilization using organic and inorganic fertilizers, pest control and irrigation channel management. (2) The ability of land to produce production by improving land quality through balanced fertilizer land management techniques and water needs for agricultural land. (3) Improving land quality through land management to improve physical, chemical and biological soil conditions and implementing crop rotation so that land quality does not decrease.